AKUNTABILITAS PENGELOLAAN DANA DESA DAN FAKTOR YANG MEMPENGARUHINYA - Zhafira, Alya; Lautania, Maya Febrianty; Yulia, Aida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
It is a responsibility of village officials to the community to manage Village Fund Allocation with accountable and transparent and also to involve the village community as much as possible so that it can guarantee that the implementation of Village fund Allocation have a full impact on community. This study aims to examine the effect of community participation, the role of village officials and the competence of human resources on the accountability of village fund management. The subjects of this research are village officials who directly manage the allocation of village funds. In total, there were 144 of research respondents were found and questioned for this research, which is consisting of village heads, village secretaries, and heads of financial affairs, all of these respondents came from 90 villages from 9 sub-districts in Banda Aceh City. Data collection was carried out using a questionnaire that was distributed directly to respondents from May to July 2021. The analytical method used was multiple linear with the SPSS version 22 application. The results showed that the variables of community participation (X1), the role of village officials (X2), and human resource competence (X3) either partially or simultaneously has a significant effect on the management and village accountability variable (Y).